Behaviour of steel beams with circular web openings under impact loading. Issue 1 (July 2020) - Al-Husainy, Alaa S.; Al-Rifaie, Ali; Ogaidi, Wael
Abstract: This paper presents a 3D nonlinear finite element analysis on simply supported steel beams subjected to impact load. The modelling was developed to simulate the beams and the models developed were validated against the corresponding experimental results with good correlation. Parametric studies were achieved to study the steel beam with web openings and to investigate the effect of several parameters such as the number of openings, impact energy and impact location on the impact response of the steel beams. The numerical predictions show that the opening presence reduced the impact force and increased the displacement. In contrast, increase the number of openings has insignificant effect on the impact behaviour within the conditions of this study. Also, higher impact energy induces the beams to exhibit higher impact force and displacement.